2017
DOI: 10.1111/adb.12498
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network deactivation to smoking cue relative to food cue predicts treatment outcome in nicotine use disorder

Abstract: Identifying predictors of treatment outcome for nicotine use disorders (NUD) may help improve efficacy of established treatments, like varenicline. Brain reactivity to drug-stimuli predicts relapse risk in nicotine and other substance use disorders in some studies. Activity in the default mode network (DMN) is affected by drug cues and other palatable cues, but its clinical significance is unclear. In this study, 143 individuals with nicotine use disorder (NUD) (male n=91, ages 18–55) received a functional MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…However, changes in the degree of connectivity between these regions have been associated with cue reactivity, nicotine dependence, and smoking cessation outcomes. For example, a study by Wilcox et al found that food cues were associated with greater deactivation of the default mode network compared with smoking cues . This is consistent with previous findings that the default mode network is less suppressed during smoking cue exposure .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, changes in the degree of connectivity between these regions have been associated with cue reactivity, nicotine dependence, and smoking cessation outcomes. For example, a study by Wilcox et al found that food cues were associated with greater deactivation of the default mode network compared with smoking cues . This is consistent with previous findings that the default mode network is less suppressed during smoking cue exposure .…”
Section: Discussionsupporting
confidence: 76%
“…The same regions are also implicated in networks at rest such as the default mode network and salience networks, which are associated with interoceptive processing and attention . Alterations in connectivity of regions involved in interoceptive processing and attention have been associated with smoking cue reactivity and smoking cessation outcomes . Exposure to smoking cues may divert attentional resources towards processing cues and trigger behavior resulting in relapse.…”
Section: Introductionmentioning
confidence: 99%
“…More robust outcome predictors are needed as, so far, few self-report measures have proven to be reliable. For example, even self-reported nicotine dependence severity shows inconsistent predictive value (Berlin et al, 2016; McPherson et al, 2014), and recent work in the same subject sample examined in the present manuscript found that a variety of predictors previously identified (mood, impulsiveness, age) were not predictive of treatment outcome (Wilcox et al, 2017). …”
Section: Introductionmentioning
confidence: 56%
“…In addition, as for smoking addiction, the precuneus is also recognized as an important contributor to cue reactivity in smokers, through its role in attentional bias toward smoking cues ( Engelmann et al, 2012 ; Courtney et al, 2014 ). The abnormal brain activity of the precuneus/DMN has also been observed in healthy smokers ( Weiland et al, 2015 ; Chen and Mo, 2017 ; Zhang et al, 2017 ; Wilcox et al, 2018 ). It should be noted that cholinergic systems play a vital role in cognitive resilience and brain plasticity ( Drever et al, 2011 ).…”
Section: Discussionmentioning
confidence: 83%